2021
DOI: 10.1038/s41598-021-96278-8
|View full text |Cite
|
Sign up to set email alerts
|

Murine neuronatin deficiency is associated with a hypervariable food intake and bimodal obesity

Abstract: Neuronatin (Nnat) has previously been reported to be part of a network of imprinted genes downstream of the chromatin regulator Trim28. Disruption of Trim28 or of members of this network, including neuronatin, results in an unusual phenotype of a bimodal body weight. To better characterise this variability, we examined the key contributors to energy balance in Nnat+/−p mice that carry a paternal null allele and do not express Nnat. Consistent with our previous studies, Nnat deficient mice on chow diet displaye… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
10
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
4
2

Relationship

1
5

Authors

Journals

citations
Cited by 8 publications
(13 citation statements)
references
References 53 publications
2
10
1
Order By: Relevance
“…1a,b and Extended Data Fig. 1a), which is distinct from the previously reported Trim28-buffered polyphenism and from other reports of heterogeneity using the Nnat +/-p allele 36,[41][42][43] . Nnat +/-p -Heavy animals were ~50% heavier than both their WT and Nnat +/-p -Light littermates and had increased white adipose tissue, spleen, pancreas, kidney, liver and heart mass (Fig.…”
Section: Resultscontrasting
confidence: 44%
See 3 more Smart Citations
“…1a,b and Extended Data Fig. 1a), which is distinct from the previously reported Trim28-buffered polyphenism and from other reports of heterogeneity using the Nnat +/-p allele 36,[41][42][43] . Nnat +/-p -Heavy animals were ~50% heavier than both their WT and Nnat +/-p -Light littermates and had increased white adipose tissue, spleen, pancreas, kidney, liver and heart mass (Fig.…”
Section: Resultscontrasting
confidence: 44%
“…Nnat loss triggers bi-stable β-cell hyperplasia. Previous work suggested that Nnat deletion causes a stochastic obesity (B6 background; several groups/vivaria 42,43 ) and partially penetrant, early-life growth restriction that is alleviated in later life through increased food intake (129S2/Sv background; one group 41 ). To capture early growth kinetics of the Nnat +/-p -Light and Nnat +/-p -Heavy animals, we tattooed animals at birth and tracked body composition.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…This increase in Npy may be the result of miR-708-5p-mediated downregulation of its target neuronatin (NNAT), a putative sarco/endoplasmic reticulum Ca 2+ inhibitor [122]. This hypothesis is supported by the fact that knockout of NNAT resulted in increased Npy expression in the ARC and an increased propensity to develop obesity in mice [123]. Transcription factors involved in the regulation of Agrp include Kruppel-like factor 4 (KLF4), activating transcription factor 3 (ATF3), STAT3, and FOXO1 [90,[124][125][126].…”
Section: The Control Of Feeding Neuropeptides By Mirnasmentioning
confidence: 98%